Pengaruh Teknologi Terhadap Penyerapan, Pendapatan, Produktivitas dan Efisiensi Usaha Pada Industri Kerajinan Genteng di Desa Pejaten - Wijaya, I Kadek Candra; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Development in the industrial sector has a very important role. Industrial development aims to create a thriving economic structure, expand employment, increase production, increase incomes, through increased human resources and technological change. This research purpose to know how the influence of technology on labour absorbtion, labour income, effort efficiency and labour productivity to pentile industry in Pejaten Village. This research uses secondary and primary data. The research site is Pejaten village of Kediri sub district Tabanan District.  Sampling method used was random sampling, and data that meet the criteria are as many as 109 samples. Discriminant analysis is a data analysis technique used in this study. Results of this research showed technology, have a significant effect on labour absorbtion, labour income, effort efficiency and labour productivity to pentile industry in Pejaten Village
Keywords: technology; absortion; income; efficiency; productivity